Mašīnbūve un metālapstrāde Latvijā (1920-1940) - Gustsons, Kristaps (Latvijas Universitāte, 2013)
Pirmā pasaules kara sākumā realizētās rūpniecības evakuācijas rezultātā jaundibinātajai Latvijas valstij bija zudusi lielākā daļa agrāko lielrūpniecības uzņēmumu. Brīvības cīņām beidzoties, rūpniecība Latvijā bija jārada praktiski no jauna. 20. gadu pirmajā pusē veiksmīgi atjaunojās arī pirms kara ievērojamā Mašīnbūve un metālapstrāde. Šī bakalaura darba mērķis ir raksturot un izvērtēt mašīnbūves un metālapstrādes lomu Latvijas Republikas tautsaimniecībā un rūpniecībā no 1920. līdz 1940. gadam. Pretēji laikam pirms Pirmā pasaules kara, neatkarīgās valsts laikā Latvijas mašīnbūve un metālapstrāde darbojās galvenokārt vietējam tirgum. Nozarē vadoša loma bija lielajiem uzņēmumiem ar vairāk nekā 50 strādniekiem. Neskatoties uz nepieciešamību importēt lielāko daļu izejvielu, 30. gadu beigās nozarei bija vērā ņemami sasniegumi, sevišķi elektrotehnikas jomā.

As a result of the evacuation of industrial enterprises during the early stages of World War One, the newly proclaimed Latvian Republic had none of the former large-scale factories. After the War of Independence the industry of Latvia had to be established anew. Among the branches of industry that revived during the first half of 1920’s was machine building and metalworking. The goal of this bachelor paper is to characterize and evaluate machine building and metal working industry in the national economy and industry of the Republic of Latvia from 1920 to 1940. Contrary to period before World War One, machine building and metalworking industry during the first independence of Latvia produced mostly for home market. Large industrial enterprises with 50 and more workers dominated the structure of this branch of industry. Despite of necessity to import a great deal of raw materials, by the end of 1930’s Latvian machine building and metalworking industry had achieved considerable progress, especially in the field of electro technical products.
Machine Building and Metalworking Industry in Latvia (1920-1940)
Keywords: Vēsture